A narrative review of the roles of topical permethrin and oral ivermectin in the management of infantile scabies. (29th June 2021) - Lobo, Yolanka; Wheller, Laura
Abstract: As standard treatments are not licensed for use in the infantile population, the treatment of scabies in this age group can be challenging. We review the relevant evidence to determine the roles of topical permethrin and oral ivermectin in the management of infantile scabies. Demographic and clinical data were collected from relevant English articles published from January 2000 to December 2020. Complete resolution was observed in 100% of infants younger than two months treated with permethrin, and 87.6% of infants aged 12 months or less and/or children weighing under 15 kg treated with ivermectin. Adverse effects from permethrin use were limited to local eczematous reactions. Adverse effects from ivermectin use included mildly elevated creatine kinase levels, eczema flare‐ups, diarrhoea, vomiting, irritability, pruritus and pustular skin reactions. Overall, both permethrin and ivermectin appear to have an acceptable safety profile in infants. Permethrin is highly effective as a first‐line therapy for scabies in infants younger than two months. Ivermectin use is recommended when authorised topical treatment has failed, in crusted scabies, in cases where compliance with topical agents may be problematic, and in infants with severely inflamed or broken skin where prescription of topical therapies would likely cause cutaneous and systemic toxicity. Additional high‐quality studies are needed to guide best practice in the management of infantile scabies.